Modelos alternativos para partículas massivas de spin 2 e gravitação massiva - Santos, Alessandro Luiz Ribeiro dos [UNESP] (2015)
Experimental data of supernova have indicated an accelerated expansion of the Universe at large distances. This has motivated the formulation of massive gravity theories, since a tiny mass for the graviton would certainly diminish the gravitational interaction at large distances without the need to introduce the dark energy. Much of the theories built for massive gravity reduce to the Fierz-Pauli model at linearized level, which is second order (in derivatives) and describes massive spin-2 particles. So it is natural to ask for possible alternative dual models to the Fierz-Pauli model. In this work we obtain alternative descriptions of massive spin-2 particles. We show that in arbitrary dimensions D ≥ 3 there are two families of linearized second order Lagrangians describing massive spin- 2 particles via a non-symmetric rank-2 tensor. We have also obtained alternative descriptions of massive spin-2 particles by an embedding procedure of the Fierz-Pauli equations of motion. All models are free of ghosts at the quadratic level, although most of them are of a higher order in derivatives. The models that we obtain can be nonlinearly completed in terms of a dynamic and a fixed metric. In the final part of this work we present two nonlinear versions of a linear model describing massive spin-2 particles, but with gauge symmetry, generalizing the topologically massive BF model, which describes massive spin-1 particles. One of the models corresponds to a bimetric model with a new derivative coupling between the metrics